The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41598-022-22680-5
|View full text |Cite
|
Sign up to set email alerts
|

Membrane mediated phase separation of the bacterial nucleoid occlusion protein Noc

Abstract: Liquid–liquid phase separation is a fundamental biophysical process to organize eukaryotic and prokaryotic cytosols. While many biomolecular condensates are formed in the vicinity of, or even on lipid membranes, little is known about the interaction of protein condensates and lipid bilayers. In this study, we characterize the recently unknown phase behavior of the bacterial nucleoid occlusion protein Noc. We find that, similarly to other ParB-like proteins, CTP binding tightly regulates Noc’s propensity to pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…26 . Additionaly, it has been reported that membranes can regulate the assembly and nucleation of condensates 14, 15 . However, to the best of our knowledge, there are no studies aiming to elucidate the mechanism behind the membrane-condensate interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 . Additionaly, it has been reported that membranes can regulate the assembly and nucleation of condensates 14, 15 . However, to the best of our knowledge, there are no studies aiming to elucidate the mechanism behind the membrane-condensate interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, membranes have been reported to control the size of intracellular condensates and modify their material properties 14 . Furthermore, the crosstalk between membranes and condensates can promote phase separation coupling in the lipid and the protein phases 15, 16, 17 also shown in cytoplasm mimicking systems 18 . In this manner, membrane-condensate interactions have become an emerging and exciting field, but important cues are still missing towards understanding the underlying mechanisms of the resulting structural changes and remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…It is straightforward to verify that the latter volume fraction is proportional to the assembly threshold defined in (11), i.e. φ = e/(1 − e) 2 ϕ * .…”
Section: Discussionmentioning
confidence: 99%
“…The biological function of both assemblies and phaseseparated compartments relies on the recruitment of specific biomolecules such as proteins, RNA or DNA [4][5][6][7]. Since assemblies and condensed phases can adhere to membrane surfaces, both not only mediate mechanisms for sorting and transport of molecules [8] but also affect the composition, shape and properties of intra-cellular surfaces [9][10][11][12]. Despite these similarities, molecular assemblies and coexisting phases also exhibit crucial differences.…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have already addressed the effect of membrane composition and phase state on the interaction with condensates 27,28 , as well as the coupling between lipid domains and condensates 29,30 , we focused on understanding the mechanism of membrane wetting and remodeling by condensates. Here, we provide a systematic analysis of the membrane remodeling and wetting behavior of GUVs exposed to water-soluble proteins that phase separate into a protein-rich and a protein-poor phase.…”
Section: Introductionmentioning
confidence: 99%